Cultural Ethos Constructed in Press Titles and Their Translation - Maria Antoniou (Romanian Journal of Communications and Public Relations, 2018)
The present study explores, from a contrastive point of view, the conditions that rule the political discourse in terms of linguistic politeness. By contrasting the data (examples drawn from press titles, mainly the French journal Le Monde Diplomatique and its’ translations into Greek), we will be able to discover the underlying operations and constraints that regulate the use of such markers and to reach conclusions about the existence or not of symmetrical uses of our two languages. The theoretical framework followed is that of Brown and Levinson and the one of the Theory of Enunciation.